Hubungan Diskusi Kelompok dengan Kemampuan Berbicara Siswa Kelas V MI Ma’arif Kalibeber - Amelia Khodijah; Nashokah Nashokah; Chairani Astina (Lembaga Yasin AlSys, 2026)
Speaking ability is an important language skill that needs to be developed among elementary school students, but observations show that some students are still less active and less confident in expressing opinions during Indonesian language learning. Although group discussion has been widely recommended as a cooperative learning strategy, studies that specifically measure its relationship with speaking ability at the madrasah ibtidaiyah level remain limited. This study aims to determine the relationship between group discussion and students’ speaking ability in the fifth-grade Indonesian language subject at MI Ma’arif Kalibeber Mojotengah in the 2025/2026 academic year. This study used a quantitative approach with a correlational design, involving 25 fifth-grade students selected through saturated sampling. Data were collected using a Likert-scale questionnaire, speaking test, observation, and documentation, then analyzed through descriptive statistics, the Shapiro-Wilk normality test, and the Spearman Rank correlation test. The results of the study show that the group discussion variable obtained a mean score of 64.56 in the good category, while speaking ability obtained a mean score of 16.12 in the good category. The results of the Spearman Rank correlation test showed a correlation coefficient of 0.983 with a significance value of 0.000 < 0.05, indicating a very strong and significant relationship between group discussion and students’ speaking ability. The conclusion of the study affirms that structured group discussion activities play an important role in strengthening students’ courage, fluency, and confidence in speaking. The implications of this study provide theoretical contributions to the development of cooperative learning and speaking skills literature, as well as practical implications for teachers and madrasahs in designing discussion-based learning to improve students’ oral communication.